Efforts to improve excellent service for Surakarta police speech therapy officers through organizational communication training - Saelan Saelan; Aria Nurahman Hendra Kusuma; Lalu M.Panji Azali; Dodiet Aditya Setyawan; Wiwik Setyaningsih; Roy Romey Daulas Mangunsong; Hafidz Triantoro Aji Pratomo (Universitas Muhammadiyah Magelang, 2024)
The main problem in organizations is ineffective communication. What we don't realize is how many organizational problems are getting more and more complicated day by day, especially human problems themselves which continue to be the main challenges that every management device must face. Important points in behavior in an organization with all the motives and desires to be achieved must be understood broadly and deeply to achieve excellent service. There are some employees who do not communicate well, which can make the service at the agency less than satisfactory. The aim of this community service activity is that participants are able to practice communication in providing excellent service. Method of community service by means of lectures, discussions and excellent service practices. As a result of this training, participants were able to practice organizational communication in excellent service with a score of 92.80.